Stylistics Analysis of Russian Advertising Slogans - Yuli Angraini (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2015)
The objectives of this study were (1) to describe types of stylistic features used in Russian advertisement slogan and (2) to interpret the writer’s intention behind it. The method of the study was descriptive qualitative. The data was collected by using Russian advertisements consist of seven advertising slogans which taken from various of Russian advertisemens in internet. The data was analyzed by using stylistic analysis specifically by using stylistics features which limited in graphology, lexicology, syntax, grammar and semantics. From the analysis and interpretation, the stylistic features in Russian advertising slogan were clear and not ambiguous. They were conveyed the way they were. They knew their audiences well as it was shown from the advertisements above.  Semantically, from one to seven advertisements , metaphor often appeared. From Lexicology,  most of the words were easy to be interpreted by the consumers, only in the part of law advertisement was a bit difficult. Syntax that the advertising slogan used commonly in the form of declarative and  imperative sentences. Grammar used in the advertisements contained suitable tenses with the moment shown in that ads.Key Words:  1. Stylistic; 2. Russian Advertising Slogans